ADMINISTRATIVE FACTORS BASED ON THE 7S FRAMEWORK AFFECTING THE EFFECTIVENESS OF EDUCATIONAL INSTITUTIONS UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFIVE OF SAMUT SAKHON SAMUT SONGKHRAM - Sornkhamron, Wanasnion; Maneechote, Tiwat (Journal of MCU Phetchaburi Review, 2026)
The purposes of this research were 1) to examine the level of administrative factors of school administrators 2) to investigate the level of school effectiveness and 3) to study the administrative factors influencing school effectiveness. The sample consisted of 295 administrators and teachers under the Secondary Educational Service Area Office Samut Sakhon and Samut Songkhram, selected by stratified random sampling based on school size. The research instrument was a questionnaire with a reliability coefficient of .900 The statistics used for data analysis included frequency, percentage, mean, standard deviation, and stepwise multiple regression analysis. The research findings revealed that 1) the overall and individual aspects of administrative factors of school administrators under the Secondary Educational Service Area Office Samut Sakhon and Samut Songkhram were at a high level 2) the overall and individual aspects of school effectiveness were also at a high level and 3) shared values, skills, and organizational structure were the administrative factors that significantly influenced school effectiveness at the .01 level. The standardized regression coefficients (β) were .318, .308, and .154, respectively. These administrative factors jointly explained 31.80 percent of the variance in school effectiveness.